Iron-based electrocatalysts derived from scrap tires for oxygen reduction reaction: Evolution of synthesis-structure-performance relationship in acidic, neutral and alkaline media. (20th November 2022) - Muhyuddin, Mohsin; Testa, Davide; Lorenzi, Roberto; Vanacore, Giovanni Maria; Poli, Federico; Soavi, Francesca; Specchia, Stefania; Giurlani, Walter; Innocenti, Massimo; Rosi, Luca; Santoro, Carlo
Abstract: Mass generation of scrap tires presents a major challenge for environmental safety, however, their upcycling into carbon-based nanomaterials by the virtue of pyrolysis treatments can open up new windows for energy conversion and storage technologies in the context of the circular economy. Herein, we report the synthesis of Fe-N-C oxygen reduction reaction (ORR) electrocatalyst for fuel cell (FC) applications using carbonaceous char derived from scrap tires through microwave-assisted pyrolysis (MAP). The char obtained from MAP was activated with potassium hydroxide and then pyrolyzed at a high temperature to fabricate Fe-N-C after mixing with iron and nitrogen precursors. Finally, the developed Fe-N-C was ball-milled and acid-etched for homogenization and leaching of iron oxide nanoparticles. In this study, structural evaluation during each synthesis step was elucidated and correlated with the ORR activity in all three pHs i.e. acidic, neutral, and alkaline. Moreover, the effect of electrocatalyst loading on ORR kinetics was also analyzed using two different loadings (0.2 and 0.6 mg cm −2 ) on the rotating ring disk electrode (RRDE). The developed Fe-N-C demonstrated encouraging onset potentials of 0.881, 0.822, and 0.936 V vs RHE in acidic, neutral, and alkaline conditions, respectively. Whereas the ORR activity was slightly reduced after the milling-etching step. Lower peroxide yield together with a tetra-electronic reduction of oxygen was witnessed in acidic and neutral conditions, however, peroxide production was increased in the alkaline medium.